Development of ligand‐coated beads to measure macrophage antimicrobial activities - Tram, TTB; Ha, VTN; Thu, DDA; Dinh, TD; Vijay, S; Hai, HT; Hanh, NT; Phu, NH; Thwaites, GE; Thuong, NTT (Wiley, 2019)
Background Information: After macrophage recognises and phagocytoses the microorganism, their phagosome undergoes a maturation process, which creates a hostile environment for the bacterium. The lumen is acidified, and proteolysis occurs to kill and degrade pathogen for further antigen presentation. It is important to understand the association between the macrophage intracellular activities and the outcome of infection. Different methods have been developed to measure the phagosome dynamics of macrophages, but there are still limitations.